Teaching and Learning English Pronunciation - Focus on Error Correction - Mazouchová, Michaela (Univerzita Pardubice, 2014)
This thesis deals with the issue of pronunciation mistakes correction in the teaching and learning processes. In the theoretical part, the current phenomenon of English as a Lingua Franca is briefly introduced and the teaching of English pronunciation is discussed. As part of the fundamental knowledge the features of English phonology are covered. In the following chapters a particular attention is devoted to the roles of a young learner and teacher, the description of mistakes, and various way of correction. Lastly, the author completes the topic with the chapters of feedback and assessment. The practical part of the thesis examines pronunciation mistakes of young learners and how they are treated by teachers. The data is than connected to the obtained teachers' attitudes and beliefs, and the effects on the classroom environment of those approaches are evaluated. The research utilises video-recorded observations and voice-recorded interviews. In the conclusion, the outcomes of the practical part are compared to the theory outlined in the theoretical part of the paper.
Výuka výslovnosti anglického jazyka se zaměřením na práci s chybou
Keywords: výslovnost; učitelé; chyby; oprava; pronunciation; teachers; mistakes; correction